Factors affecting gross domestic product in Malaysia / Muhammad Azri Shahizan Mohd Zamhor - Mohd Zamhor, Muhammad Azri Shahizan (Faculty of Business and Management, 2018)
Gross Domestic Product (GDP) growth has always been treated as current issue that studied by many researchers. Inconsistency growth of GDP per capita within a country will lead to higher incidence of poverty as well as delay the progress in health, education, crime and eventually the economic growth. The factors towards GDP growth are relatively important to prevent the occurrence of socio-political instability. This paper investigates the relationship between Gross Domestic Product (GDP) growth and the other factors such as Credit to Private Sector (CPS), Domestic Investment (DI), Labour Force (LAB), Human Capital (HC) and Money Supply (MS) in Malaysia. Annual time series data for the 1970 to 2014 periods, the Autoregressive Distributed Lag (ARDL) and Unit Root Test such as Augmented Dickey Fuller (ADF) and Phillips Perron (PP) are used for the analysis. The results reveal that among the factors of DI, LAB, HC and MS have positive significant impact on GDP growth. However, CPS is the only variable that contributes significantly negative to GDP growth in Malaysia. Based on the result, it is recommended by sustaining the stability on money supply by implementing an appropriate monetary policy as it will directly impact the size and growth rate of the money supply, which impacts the interest rates in economy which able to enhance GDP growth, identify solutions for current economic problems.